Continuous flow modulates zein nanoprecipitation solvent environment to obtain colloidal particles with high curcumin loading. (January 2023) - Guo, Haocheng; Feng, Yiming; Deng, Yong; Yan, Tianyi; Liang, Zimo; Zhou, Yichen; Zhang, Wei; Xu, Enbo; Liu, Donghong; Wang, Wenjun
Abstract: Differences in supersaturation rates may cause stepwise precipitation of active ingredients and colloidal particles, thus producing low loading capacity vehicles. Shortening the mixing time of the solvent and the antisolvent is a strategy to achieve almost simultaneous supersaturation of the active ingredients and the colloidal particles. In this study, electrostatic co-assembly process of zein and sodium hyaluronate (SH) was used to embedding curcumin. The ethanol-water laminar diffusion with controlled mixing time (102.06–13.23 ms) was obtained by changing the flow ratios (8–24) using a flow-focused microfluidics chip. The particle size of zein-SH nanoparticles decreased from 319.3 ± 1.7 nm to 79.8 ± 0.7 nm with the increase of flow ratio (8–24). Continuous flow prepared zein-SH nanoparticles showed more ordered secondary structures than bulk mixing. Bulk mixing prepared curcumin-embedded samples also presented dendritic crosslinking, with 0.4 ± 0.5% loading capacity due to curcumin precipitation earlier than colloidal particles supersaturation. However, with millisecond mixing time, a high flow ratio prepared sample (∼77 nm) showed 97.2 ± 0.6% encapsulation efficiency, 11.1 ± 0.1% loading capacity, and significantly better bioaccessibility in the in-vitro gastrointestinal digestion. According to the FTIR and XRD analysis, curcumin can be embedded into zein-SH nanoparticles through hydrophobic interactions and hydrogen bonds. The millisecond antisolvent time provided by continuous flow offers the possibility of tuning the secondary structure and improving loading capacity during the electrostatic co-assembly of colloidal particles. Graphical abstract: Image 1 Highlights: Continuous flow sub-milliseconds mixing to supersaturate zein and curcumin. Flow ratio modulates secondary structures of zein during antisolvent precipitation. Continuous flow curcumin loading capacity was much higher than bulk mixing.